No detectable carotenoid concentrations in serum of llamas and alpacas. Issue 4 (9th November 2016) - Raila, J.; Schweigert, F. J.; Stanitznig, A.; Lambacher, B.; Franz, S.; Baldermann, S.; Wittek, T.
Summary: Carotenoids are lipid‐soluble pigments and important for a variety of physiological functions. They are major dietary vitamin A precursors and act as lipophilic antioxidants in a variety of tissues and are associated with important health benefits in humans and animals. All animals must acquire carotenoids from their diet, but to our knowledge, there are no studies investigating the intestinal carotenoid absorption and their blood concentrations in New World camelids. The present study aimed to assess the serum concentrations of selected carotenoids in llamas ( n  =   13) and alpacas ( n  =   27). Serum carotenoids as well as retinol (vitamin A) and α ‐tocopherol (vitamin E) were determined by high‐performance liquid chromatography coupled with mass spectrometry and these were unable to detect any carotenoids ( α ‐ and β ‐carotene, α ‐ and β ‐cryptoxanthin, lutein, zeaxanthin, lycopene) in the samples. The concentrations of retinol in alpacas (2.89 ± 1.13  μ mol/l; mean ± SD) were higher (p   =   0.024) than those found in llamas (2.05 ± 0.87  μ mol/l); however, the concentrations of α ‐tocopherol were not significantly (p   =   0.166) different (llamas: 3.98 ± 1.83  μ mol/l; alpacas: 4.95 ± 2.14  μ mol/l). The results show that both llamas and alpacas are not able to absorb intact carotenoids, but efficiently convert provitamin A carotenoids to retinol.